The effect of correlation of uncertainties on collaborative optimization of integrated energy system - Yu Fu (Elsevier, 2021)
Integrated energy system is an effective alternative to provide low-carbon sustainable energy to meet growing and complex energy demands. Uncertainty has a great impact on system configuration and operation schedule and the correlation between uncertain parameters increases the difficulty of high-precision optimization and control under this background. Thus, this paper focus on the correlation of uncertainties using copula theory and analyze the effect of correlation on optimization results. The case study shows that considering the correlation between uncertain parameters can affect the optimization results of the system not only in configuration but also the operation characteristics and reduce the total cost of the system.